History of India : From the sixteenth centuary to the twentith century - Spear, Percival (New Delhi Penguin Books, 2003)
This second volume of a classic introduction to India's history deals with the Mughal and British periods, tracing the continuities that pervaded them. Mughal rule is seen as the precondition for the modern age ushered in by the British, and the Raj as the harbinger of Western civilization in India.
Keywords: INDIAN HISTORY; BRITISH RULE-INDIA; MUHAL HISTORY; MODERN INDIA; ARCHITECTURE BY REGION (AR-REG)